Integrationsregime in der Arbeitswelt Eine Ethnographie migrantischer Praktiken der Selbstständigkeit in Norditalien - Pierdicca, Marika (Büchner-Verlag, 2022)
Marika Pierdicca's doctoral thesis provides an ethnography of migrant self-employment in northern Italy and highlights the link between an increasing neoliberalization of labor and notions of "integration." The study questions integration as an affirmative concept and problematizes structural forms of differential inclusion, racialization, and ethnicization of contemporary labor relations. A genealogical reconstruction of Italian migration policies illustrates how the "integration regime" acts simultaneously as a selection management and as a border regime. Against the backdrop of an understanding of self-employment as a life concept, Pierdicca performs a biopolitical analysis of labor narratives and experiences of the protagonists in the field. Her research deals with approaches to affective labor critical of capitalism, considers the integration regime as a laboratory of neoliberal subjectivation, and thereby elaborates specific forms of labor exploitation.